SISTEM INFORMASI PEMBAYARAN SPP BERBASIS WEB MENGGUNAKAN METODE RAD (RAPID APPLICATION DEVELOPMENT) DI SMK MUHAMMADIYAH KAWALI - Yudi Permana, Nana; Seftian, Luki; Sidiq, Maulana (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2025)
The goal of this project is to establish a web-based SPP payment system in order to provide a digital solution. Designing and developing an application that can streamline the payment process for parents and students while simultaneously increasing the precision and efficiency of the school's financial data management is the primary goal. The research employs the Rapid Application Development (RAD) technique in order to accomplish this goal. Because of its emphasis on quick and iterative development cycles, this approach was selected.A variety of potent web technologies were used in the design and construction of the payment system. The PHP programming language was utilized for the back-end, which handles logic and data processing.